INFLUENCE OF ATTACHMENT STYLES ON ESTABLISHMENT OF ADOLESCENTS’ SELF ESTEEM AMONG SECONDARY SCHOOL STUDENTS FROM BLENDED FAMILIES IN KIAMBU COUNTY - Lucy Gachenia; Ruth Kamunyu; Nathan Chiroma (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Attachment styles adopted by parents are essential in development of adolescent psychosocial wellbeing. This phenomenon is more profound in blended families where there are multiple relationships that can lead to many challenges. However, with appropriate attachment styles adopted by step parents such challenges can be mitigated. The purpose of this study was to assess the influence of attachment styles on adolescents’ self-esteem among secondary school students from blended family in Kiambu County, Kenya. Attachment theory by Bowlby guided this study. The study adopted a mixed method approach, descriptive causal effect design and pragmatic paradigm to guide the study. Multi-stage sampling method and inclusive /exclusive criteria were used. Firstly the study adopted survey method as the sampling technique because the total population of adolescents that came from blended families was unknown. Simple random sampling was used to select 9 schools and also determine the 5 classes to be sampled in each of these schools. The 5 classes had a population of 55 students each. A short questionnaire with demographic data of students was issued to all the students (2475) in a bid to elicit the adolescents from the said classes that came from blended families in the 9 schools. A total number of 208 adolescents from blended families in the 9 schools was elicited and this was considered a sufficient sample size. In addition, simple random sampling was used to sample 24 respondents to form 4 focus groups while purposive sampling was used to sample 4 counsellors from 9 schools for in-depth interview. Data was collected using questionnaires, counsellors’ interview schedule and focus group discussions. Inventory for Parent and Peer Attachment Scale and Rosenberg Scales were used as measuring tools. Data was analysed through descriptive statistics, statistical assumption tests, correlation tests- T- test and ANOVA analysis while qualitative data was analysed by use of narrative analysis. Findings were presented in form of tables while interview data was presented in narrative form. Permission to conduct the study was obtained from the National Council for Science and Technology, the Kiambu County Government, Ethical approval was sought from accredited IERC (Institutional Ethics Review Committee) as well as a written informed consent from the school administration. Results indicated that attachment styles adopted by step parents influence the establishment of adolescent self- esteem. The study will benefit Ministry of Education, counsellors, parents, families and society.